The distribution of the burden of taxation from the point of view of equity - Mateusz Langer (Prawo Budżetowe Państwa i Samorządu)
The goal of this paper is to clarify the basic point of view of equity from a perspective of modern finance theory. The author strives to determine whether, and if so, what role does the equity at distribution of the burden of taxation in the state. In particular, research has shown in a broader context the basic approach to get the point of equity, and innovative conceptuality as a reflex of the values and postulates of law. The material in this article is an interdisciplinary investigation of equity as a quite important and complex issue of theory, philosophy and practice of law.